In Silico Molecular Interaction Analysis and Pharmacokinetic Profiling of Flavonoids from Catharanthus roseus (Flower) Against TXNIP Protein - Pushpa, Ramya Ranjan Nayak Santosh; Babulal, Kiran Sharma; Kumaran, Rajendran; Shoba, Gunasekaran; Balakumaran, Manickam Dakshinamoorthi (Trends in Sciences, 2022)
Catharanthus roseus is a flowering plant whose flowers have been used in traditional medicine to treat diabetes mellitus. Some of the flavonoids present in these flowers, namely, quercetin, petunidin, malvidin, kaempferol, and hirsutidin were utilized for studying molecular interaction analysis. Diabetes mellitus which is a metabolic disorder caused by the depletion in the secretion of insulin, which regulates the blood glucose levels by facilitating the metabolism of glucose. Reduction in insulin secretion is often caused by the loss of beta cells of the pancreas. Thioredoxin-interacting protein (TXNIP) is an alpha arrestin which inhibits the production of thioredoxin. It can regulate the beta cells and its inhibition can be advantageous. Reduction in insulin secretion is often caused by the loss of beta cells of the pancreas. Studies have shown that elevated levels of TXNIP can induce apoptosis in beta cells while deficiency of TXNIP leads to protection against Type I & II diabetes due to beta cell survival. To study molecular interactions, flavonoids from the flower of C. roseus and control drug glibenclamide were subjected to docking against 3D structure of TXNIP protein using Autodock 4.2 and their molecular interactions were visualized using a Biovia discovery studio visualizer. Docking interactions and ADMET studies of the bioactive compounds signified the application of C. roseus as a natural therapeutic agent to combat diabetes. HIGHLIGHTS Studies have shown elevated levels of TXNIP can induce apoptosis in beta cells while deficiency of TXNIP leads to protection against diabetes type I & II due to beta cell survival Molecular interaction analysis of flavonoids namely, quercetin, petunidin, malvidin, kaempferol, and hirsutidin from Catharanthus roseus (Flower) against TXNIP Protein were utilized for studying using Autodock 4.2 software ADMET study of the selected bioactive compounds were carried out Docking interactions and ADMET studies of the bioactive compounds signified the application of roseus as a natural therapeutic agent to combat diabetes GRAPHICAL ABSTRACT